Pendidikan Agama Islam Untuk Mantan Pencandu Narkoba - Syamsul Muqorrobin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This research aims to analyze Islamic Religious Education for Former Drug Addicts. The type of research used is literature review. Data retrieval techniques with documentation from journal data on Google Schoolar. Data analysis technique using Systematic Literature Review. The research results of Islamic Religious Education have an important role in guiding former drug addicts to gain a deep spiritual and moral understanding. Through Islamic values, such as piety, discipline, and tolerance, religious education can help them rebuild their lives with a strong foundation. Learning about justice, compassion and social responsibility in Islam can also help them overcome drug addiction problems in a holistic way. By understanding the principles of the Islamic religion, former drug addicts can absorb positive values ​​and receive spiritual support that can guide them towards positive changes in their lives.